Analysis Legal About Action Criminal Fraud Thrifting - Triantari, Verginia Adzraa; Khalid, Hasbuddin; Hambali, Azwad Rachmat (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the enforcement of criminal law in handling cases of second-hand clothing fraud (thrifting). Additionally, it seeks to identify and analyze the factors contributing to such fraudulent activities. This study employs a normative-empirical research method. It applies a literature review approach by examining various legal materials, which are categorized into primary legal materials, such as laws and regulations; secondary legal materials, including books, legal journals, and previous research related to this study; and tertiary legal materials, which serve as supplementary references. The findings of this study indicate that second-hand clothing fraud (thrifting) is regulated under Article 378 of the Criminal Code, which defines fraud as an act of deception or dishonesty for personal gain, punishable by up to four years of imprisonment. Online fraud is addressed in Article 28 of the ITE Law, while Article 47(1) of the Trade Law outlines criminal penalties for importers who illegally import used goods. The factors influencing second-hand clothing fraud (thrifting) include the lack of government supervision despite the many prohibitions on the import of second-hand clothing, as well as insufficient public awareness campaigns regarding the legal consequences of such fraud. Based on these findings, this study provides two key recommendations: first, buyers should verify the credibility of sellers before making a transaction and use a secure platform. second, local governments should raise public awareness about the risks of fraud and imported bans while also providing information about the health risks associated with used clothing.